2018
DOI: 10.4274/tjh.2018.0071
|View full text |Cite
|
Sign up to set email alerts
|

Does Reinfusion of Stem Cell Products on Multiple Days Affect Engraftment?

Abstract: Objective:High-doses of melphalan treatment with autologous stem cell transplantation in multiple myeloma (MM) remains a major treatment modality in suitable patients. A minimal dose of 2x106/kg CD34+ cells is preferred to achieve engraftment. Some patients need multiple leukapheresis procedures to achieve the necessary number of CD34+ cells, but this can cause a high volume of stem cell product that cannot be given in a single day. Whether or not the number of infusion days affects engraftment has not been st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…The infusion of CD34 + HPCs above 2 × 10 6 /kg is usually the recommended dose to prevent engraftment failure or late recovery [5,6]. There are studies that have shown that administering <5 × 10 6 /kg of CD34 + HPCs prolongs the engraftment time and, especially, adversely affects platelet recovery [7]. The International Myeloma Working Group (IMWG) recommends that an average of 8 × 10 6 /kg CD34 + should be given if mobilized, and that the minimum administration target should be 4 × 10 6 /kg CD34 + progenitor cells [8].…”
Section: Introductionmentioning
confidence: 99%
“…The infusion of CD34 + HPCs above 2 × 10 6 /kg is usually the recommended dose to prevent engraftment failure or late recovery [5,6]. There are studies that have shown that administering <5 × 10 6 /kg of CD34 + HPCs prolongs the engraftment time and, especially, adversely affects platelet recovery [7]. The International Myeloma Working Group (IMWG) recommends that an average of 8 × 10 6 /kg CD34 + should be given if mobilized, and that the minimum administration target should be 4 × 10 6 /kg CD34 + progenitor cells [8].…”
Section: Introductionmentioning
confidence: 99%